The Effect of Using Recycled Aggregates on Concrete Durability Indicators (Acid Attack and Salt Immersion) - علي خيربك; بسام حسن; باسل أصلان (Latakia University Journal -Engineering Sciences Series, 2023)
The issue of recycling is of great importance globally, as a result of the increase in waste of all kinds, and most countries have worked on recycling industrial and natural waste in order to benefit from it again and reduce the large financial burdens resulting from the transportation and disposal operations, in addition to the cost of manufacturing these products themselves, and in recent years the reason for the size of The large rubble resulting from the demolition of buildings is the largest area for thinking about recycling these rubble with the aim of re-using them again and starting to use them in road paving works. Preliminary results of the use of recycled aggregates gave encouraging values that made it possible to use them in concrete. The greatest concern of researchers was the ability of these recycled aggregates to perform for a long time in concrete. Previous studies indicate a decrease in the resistance values when the replacement rates are increased. As for the durability studies, they are relatively few, as they require a long time and advanced techniques to probe the structure of concrete after exposure to destructive conditions in order to determine its lifespan. From here it was necessary to study the change of the properties of this concrete with time and to study its durability under the influence of many factors such as the effect of destructive materials (acids and salts) and to measure the extent of the effect of replacing natural stones with recycled stones on the durability properties. The results of the research show good values for durability indicators of concrete manufactured using recycled aggregates compared to concrete manufactured from natural aggregates only. Durability indicators improve up to 50% replacement rate with regard to immersion in acids and chlorides solution.